Gestión administrativa y su influencia en el proceso comercial de la empresa familiar en la ciudad de Quevedo, año 2015 - Varela Peralta, Betty Luciola (2015)
This research projects into a detailed analysis in the "Administrative Management Family Business" City Quevedo Los Rios Province, to provide comprehensive information, through the analysis of the different life stages of an enterprise, levels strategies, perspectives, ethics and competitiveness, the challenges of the XXI century. The main objective of the project is to be a support base for family business managers, to plan, organize, direct and control, human and financial resources efficiently. Management in family businesses is presented empirically where 92% of his administration's family, as wife, sons, nephews, etc. In addition 78% of companies do not have a future strategic plans with measurable and achievable targets, 85% of companies do not prepare for the succession of command, and this, a key to the development and continuity of the organization factor, since according to studies 30% survive to the second generation and from there only 5% of family businesses make it to the third generation, 61% of decisions are taken by the manager or owner, thus closing the possibility of seeking other expert opinions regarding business professionals, for this there are many variables that could explain these figures, several companies are small and lack the financial resources and personnel to face competition and at the same time to stay much longer This means, for it was taken as regards the study of the administration of several family businesses, to address all major components within the business process. Keywords: Family Business, Administrative Management, Stay, Business Process.